Immunologic “Cold” Squamous Cell Carcinomas of the Head and Neck Are Associated With an Unfavorable Prognosis - Ribbat-Idel, Julika; Perner, Sven; Kuppler, Patrick; Klapper, Luise; Krupar, Rosemarie; Watermann, Christian; Paulsen, Finn-Ole; Offermann, Anne; Bruchhage, Karl-Ludwig; Wollenberg, Barbara; Idel, Christian (Frontiers in Medicine, 2021)
(1) Background: Head and neck squamous cell carcinoma (HNSCC) represents a common cancer worldwide. Past therapeutic advances have not significantly improved HNSCC prognosis. Therefore, it is necessary to further stratify HNSCC, especially with recent advances in tumor immunology. (2) Methods: Tissue microarrays were assembled from tumor tissue samples and were complemented with comprehensive clinicopathological data. H&E whole slides from resection specimen were categorized according to their immune cell infiltrate as “hot”, “cold”, or “excluded”. (3) Results: Investigating tumor immune cell patterns, we found significant differences in survival rates. Immunologic “hot” and “excluded” HNSCCs are associated with better overall survival than “cold” HNSCC patients (p < 0.05). Interestingly, the percentage of all three patterns is nearly identical in p16 positive and negative HNSCCs. (4) Conclusions: Using a plain histological H&E approach to categorize HNSCC as being immunologic “hot”, “cold” or “excluded” can offer a forecast of patients' prognosis and may thus aid as a potential prognostic tool in routine pathology reports. This “hot-cold-excluded” scheme needs to be applied to more HNSCC cohorts and possibly to other cancer types to determine prognostic meaning, e. g. regarding OS or DFS. Furthermore, our cohort reflects epidemiological data in the national, European, and international context. It may, therefore, be of use for future HNSCC characterization.